Lincoln's way : how six great Presidents created American power - Striner, Richard, 1950- (Rowman & Littlefield Publishers, 2010)
The debate is as old as the American Republic and as current as this morning's headlines. Should a president employ the powers of the federal government to advance our national development and increase the influence and power of the United States aroundthe world? Under what circumstances? What sort of balance should the president achieve between competing visions and values on the path to change? Over the course of American history, why have some presidents succeeded brilliantly in applying their power and influence while others have failed miserably? In Lincoln's Way, historian Richard.